Серый меч - Эльтеррус Иар (Ленинградское издательство, 2010)
Экземпляры: ф.2 (20240930) / Инвентарный номер: 65108 / Цена: / Сис.шифр: 84(2=411.2)6-4 / Авт.знак: Э 53 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6-445.1